N-acetylglutamic acid alleviates oxidative stress based on histone acetylation in plants - Hirakawa, Takeshi; Tanno, Seia; Ohara, Kazuaki (Frontiers in Plant Science, 2023)
Oxidative stress causes cellular damage and genomic instability through the accumulation of reactive oxygen species (ROS) in plants, resulting in reduced crop production. Chemical priming, which can enhance plant tolerance to environmental stress using functional chemical compounds, is expected to improve agricultural yield in various plants without genetic engineering. In the present study, we revealed that non-proteogenic amino acid N-acetylglutamic acid (NAG) can alleviate oxidative stress damage in Arabidopsis thaliana (Arabidopsis) and Oryza sativa (rice). Exogenous treatment with NAG prevented chlorophyll reduction induced by oxidative stress. The expression levels of ZAT10 and ZAT12, which are regarded as master transcriptional regulators in response to oxidative stress, increased following NAG treatment. Additionally, Arabidopsis plants treated with NAG showed enhanced levels of histone H4 acetylation at ZAT10 and ZAT12 with the induction of histone acetyltransferases HAC1 and HAC12. The results suggest that NAG could enhance tolerance to oxidative stress through epigenetic modifications and contribute to the improvement of crop production in a wide variety of plants under environmental stress.